Rapamycin-resistant phosphorylation of the initiation factor-4E-binding protein (4E-BP1) in v-SRC-transformed hamster fibroblasts - Tuhácková, Z; Sovová, V; Sloncová, E; Proud, C G (International journal of cancer, 1999)
Increased phosphorylation of the translational repressor protein 4E-BP1 was found in the cell line derived from the tumor induced in Syrian hamster by Rous sarcoma virus (RSV). This was accompanied by its dissociation from the complex with initiation factor eIF4E. The ribosomal S6 protein kinase p70S6k is supposed to be regulated by the same or a closely related rapamycin-sensitive signalling pathway to that which modulates 4E-BP1. Phosphorylation and activity of p70S6k were found to be also increased in RSV-transformed H19 cells that express significantly higher amounts of the Src protein (p60src) relative to the non-transformed hamster fibroblasts NIL-2. The increased activity and phosphorylation of p70S6k were blocked by rapamycin, indicating that the rapamycin-sensitive pathway is involved in its regulation in v-src-transformed hamster fibroblasts. In agreement with this, rapamycin reduced the expression of elongation factor eEF1alpha (whose translation is regulated by a rapamycin-sensitive mechanism thought to involve p70S6k) and did not affect the production of a housekeeping protein, alpha-tubulin, in these cells. Synthesis of Src protein was also inhibited in cells treated with rapamycin. However, treatment of cells with a concentration of rapamycin sufficient to completely inhibit the activity and phosphorylation of p70S6k resulted in only partial de-phosphorylation of 4E-BP1 and its re-association with eIF4E in the transformed cells, indicating that additional rapamycin-insensitive mechanisms/pathways are implicated in the control of 4E-BP1 phosphorylation in RSV-transformed hamster fibroblasts. Over-expression of eIF4E favours cell proliferation and can lead to a transformed phenotype, while over-expression of 4E-BP1 has the opposite effect. The altered signalling to the phosphorylation of 4E-BP1 in RSV-transformed cells, which leads to its dissociation from eIF4E and thus relief of inhibition of eIF4E function, may therefore represent an important regulatory mechanism in malignant cell growth.
Keywords: kur domácí; Animals; transportní proteiny; křečci praví; fosfoproteiny; kinasy ribozomálního proteinu S6; Chickens; Cell Line, Transformed; Genes, src; Phosphoproteins; viry ptačího sarkomu; nádorové buňky kultivované; elongační faktor 1; Peptide Elongation Factors; Cell Transformation, Neoplastic; regulace genové exprese; Carrier Proteins; Tumor Cells, Cultured; fosforylace; Sirolimus; iniciační faktory; Peptide Elongation Factor 1; elongační faktory; Avian Sarcoma Viruses; Ribosomal Protein S6 Kinases; nádorová transformace buněk; sirolimus; Peptide Initiation Factors; Gene Expression Regulation; zvířata; transformované buněčné linie; geny src; Phosphorylation; Cricetinae